Construção de identidade na produção residual de Raquel Naveira - Leitão, Mary Nascimento da Silva (2018)
From the study of the poetic work of Raquel Naveira, one can observe the recurrence of some themes that contribute to the identity formation of the poet from Mato Grosso do Sul. Memories of the homeland, religious influences, the rescue of classical mythology, and the defense of women are examples of recurring issues in their literary production.Among the investigated themes, we found the presence of two central subjects that cross the whole work: the feminine and the cultural hybridization. The contents guide an identity that is built both collectively, in a sociocultural context, and individually, considering the process of endoculturation. In this case, we also dedicate ourselves to the deepening of the conception of ethos, that is, the image constructed by the poet himself, considering the insubmiss aspect of his writings.Thus, we highlight as main objectives: a) to present panoramically the poetic work of Raquel Naveira, in order to disseminate her literary production for different public readers; b) To analyze poetic texts highlighting the social arguments that guide them; c) to construct an identity profile of a contemporary author. It is a comparative analysis between literary and historical texts that has as main support the theory of residuality, whose purpose is to investigate the traces of mentalities of other epochs remaining in the current literary productions. Among the theorists who contributed to the present research, we can mention: Hilário Franco Júnior (imaginary), Raymond Williams (culture), Peter Burke (cultural hybridity), Michelle Perrot (feminine), Roberto Pontes (poetry insubmiss, residuality) and Dominique Maigueneau (ethos). We consider all the conceptions presented essential to the understanding of the work of the author from Mato Grosso do Sul. His poetic texts, illustrated in the theoretical interspersions, are threads that unite in the construction of an insubmissa identity.